(untitled) (Research, Society and Development, 2021)
The objective of this study is to evaluate the influence of five feed restriction programs (FRP) on broiler performance and carcass yield. 425 Cobb 500® broilers were distributed in a completely randomized design with five FRPs and five replicates with 17 broilers. The FRPs were: Program 1 (P1): consumption ad libitum (AL) of control diet from 14 to 42 days; P2: quantitative restriction (QTR) of 10% of AL consumption from 14 to 28 days and AL consumption from 29 to 42 days; P3: AL consumption from 14 to 28 days and QTR from 29 to 42 days; P4: qualitative restriction (QLR) of 10% of the level of crude protein and essential amino acids from 14 to 28 days and AL consumption from 29 to 42 days; and P5: AL consumption from 14 to 28 days and QLR from 29 to 42 days. The broilers of the AL treatment gained more weight (p≤0.01), but had a similar FCR (P>0.05) compared to broilers submitted to QTR from 29 to 42 days. In addition, broilers fed QTR from 14 to 28 days presented a lower FI and a better FCR (p≤0.01) in relation to broilers fed QLR of 14 to 28 (P4) and 29 to 42 days (P5). The broilers fed QTR of 14 to 28 days diet presented a similar FCR as broilers fed AL. The 10% reduction in AL consumption of 14 to 28 d is a viable economical alternative to feed broilers up to 42 days of age.